Differential Effects of Serotonin Transporter Genotype on Anxiety-Like Behavior and Cognitive Judgment Bias in Mice - Krakenberg, Viktoria; von Kortzfleisch, Vanessa Tabea; Kaiser, Sylvia; Sachser, Norbert; Richter, S. Helene (Frontiers in Behavioral Neuroscience, 2019)
In humans, the short allele of a common polymorphism in the serotonin transporter (5-HTT) gene is associated with a higher risk to develop depression and anxiety disorders. Furthermore, individuals carrying this allele are characterized by negative judgment biases, as they tend to interpret ambiguous information in a more pessimistic way. 5-HTT knockout mice, lacking the 5-HTT gene either homo- or heterozygously, provide a widely used model organism for the study of symptoms related to human anxiety disorders. In the present study, we aimed to prove the anxiety-like phenotype of the 5-HTT mouse model, and to investigate whether 5-HTT genotype also causes differences in judgment bias. While our results confirm that homozygous 5-HTT knockout mice display highest levels of anxiety-like behavior, it was decreased in heterozygous mice. Against our expectations, we did not detect differences in the animals’ judgment bias. These results indicate that at least in mice the association between 5-HTT genotype and judgment bias is not straightforward and that other factors, including multiple genes as well as environmental influences, are implicated in the modulation of judgment biases. More research is needed to gain further insights into their function as potential endophenotypes for psychopathology.